2018
DOI: 10.1007/s11136-018-1845-0
|View full text |Cite
|
Sign up to set email alerts
|

Coping mediates the relationship between sense of coherence and mental quality of life in patients with chronic illness: a cross-sectional study

Abstract: PurposeThe aim of the present study was to investigate relationships between sense of coherence, emotion-focused coping, problem-focused coping, coping efficiency, and mental quality of life (QoL) in patients with chronic illness. A model based on Lazarus’ and Folkman’s stress and coping theory tested the specific hypothesis: Sense of coherence has a direct and indirect effect on mental QoL mediated by emotion-focused coping, problem-focused coping, and coping efficiency in serial adjusted for age, gender, edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 46 publications
8
51
0
3
Order By: Relevance
“…Other studies have reported that the experience of being in control of one's health situation is important for QoL in chronic illness (Kristofferzon et al . 2018). Understanding health information well enough to know what to do may provide CKD patients with a feeling of control and thereby reduce stress.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that the experience of being in control of one's health situation is important for QoL in chronic illness (Kristofferzon et al . 2018). Understanding health information well enough to know what to do may provide CKD patients with a feeling of control and thereby reduce stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the importance of considering the different components of SOC, Antonovsky4 9 strongly highlights the indivisibility of the construct. The literature indicates that SOC is related to an individual’s ability to identify and (re)use resources from his/her internal (eg, cognitive, emotional and behavioural strategies) or external (eg, social support, social fairness, relationships, outdoor life, culture) environment to cope with difficulties and maintain good health 10–13. According to Antonovsky,4 6 individuals with high SOC perceive stressors as challenges, and thus anticipate events and the resources available to modify their perception of life and move from a condition of illness to one of health.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] We explored the construct of peace of mind in a sample of AYAs with newly diagnosed cancer; our hypothesis was that peace of mind is a dimension of mental quality of life that may be vulnerable to the disruption and stress imposed by illness. 18 In keeping with Lazarus and Folkman model, we conceived of the cancer diagnosis as the primary stressor. Appraisal of the threat of the disease includes issues such as patient perception of prognosis, whereas potential coping resources include internal psychological resources (versus psychological challenges such as depression and anxiety), relationships within and outside of the medical team, and a personal sense of ownership and control in the form of decisional engagement.…”
Section: Introductionmentioning
confidence: 99%